Impact of COVID-19 on Singapore human resource practices - Easwaramoorthy Rangaswamy; Nishad Nawaz; Elaine Lu (Cogent Business & Management, 2024)
The COVID-19 pandemic has completely changed the landscape of organisations, which requires HR professionals to work closely with management to adapt to transformational changes. This research aims to study the impact of COVID-19 on HR practices in Singapore, focusing on remote work and communication. Realism and a deductive approach have been adopted in this Descriptive quantitative research, with the survey as the research strategy to explore remote work experiences and communications during COVID-19 in Singapore. As a cross-section study, the online questionnaire was used to collect responses from 102 employees with different backgrounds from different organisations and industries. It was found that almost half of the employees felt that the impact of COVID-19 on them was moderate, with more than 70% of employees working from home. Employees felt that government advisory was the most important information, and organisations effectively responded to COVID-19 updates. In the post-COVID-19 era, future scholars should consider what organisations and human resource departments must prepare when employees return to the office. Research contributions and implications include recommendations for remote work practices, implementation of partial remote work, good work schedule to improve efficiency and recommendations for communication practices, upgradation of IT systems and skills.
Keywords: 650; COVID-19; Human resource practices; remote working; work from home; remote work effectiveness; remote work challenges